Analisis Strategi Pemasaran Tabungan Hijrah Haji Dalam Meningkatkan Jumlah Nasabah Pada Bank Muamalat KCP Nganjuk - Devi Novitasari; Dedi Suselo (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
The purpose of the study is to analyze the planning, implementation, evaluation, and recommendation of marketing strategies in increasing the number of customers at Bank Muamalat KCP Nganjuk during the pandemic. This research method uses descriptive qualitative. The primary and secondary data collection techniques were interviews, observation, and documentation. The results of the research state that marketing strategy planning during the pandemic is by adding marketing channels and focusing on promotion through digitalization. The most effective marketing strategy is personal selling; in addition, Bank Muamalat also conducts promotion through direct selling, brochures, and social media. The strategy that has been implemented has been going well, but there are several obstacles faced. The solutions offered include adding marketing channels, offering a multi-purpose Hajj financing program, and opening a savings account for the Hajj plan. The marketing strategy recommendation is that banks must be able to take advantage of current opportunities, increase their promotions both through social media and direct pick-ups, and maintain good relations with parties who have collaborated.